Embryonic stem cell gene targeting using bacteriophage lambda vectors generated by phage-plasmid recombination. - Tsuzuki, T (1998)
Targeted mutagenesis is an extremely useful experimental approach in molecular medicine, allowing the generation of specialized animals that are mutant for any gene of interest. Currently the rate determining step in any gene targeting experiment is construction of the targeting vector (TV). In order to streamline gene targeting methods and avoid problems encountered with plasmid TVs, we describe the direct application of lambda phage in targeted mutagenesis. The recombination-proficient phage vector lambda2TK permits generation of TVs by conventional restriction-ligation or recombination-mediated methods. The resulting lambdaTV DNA can then be cleaved with restriction endonucleases to release the bacteriophage arms and can subsequently be electroporated directly into ES cells to yield gene targets. We demonstrate that in vivo phage-plasmid recombination can be used to introduce neo and lacZ - neo mutations into precise positions within a lambda2TK subclone via double crossover recombination. We describe two methods for eliminating single crossover recombinants, spi selection and size restriction, both of which result in phage TVs bearing double crossover insertions. Thus TVs can be easily and quickly generated in bacteriophage without plasmid subcloning and with little genomic sequence or restriction site information.